Child labor under Islamic law (the shari’ah): an overview - Mohd, Azizah; Nik Mahmod, Nik Ahmad Kamal; Ali Mohamed, Ashgar Ali; Amuda, Yusuff Jelili; Che Mohd Salleh, Marhanum (IIUM Press, International Islamic University Malaysia, 2018)
Child Labor is another serious world phenomenon that affects a child’s rights. In general, Child Labor may seem to reflect any form of child employment scenario whether it hazardous or not- hazardous to children’s welfare. Millions of children are working around the world for helping their destitute family or themselves. It is so unfortunate that many are also forced to involve in dangerous employment like armed forces, drug trafficking and sexual exploitation. This clearly violates children rights especially right to kind treatment, maintenance, good health and education. In Islam, children are regarded as bounties from Allah the almighty God and should be loved and cherished. This paper wishes to examine Islamic Overview on Child Labor and how they are to be protected. Examination extends to certain means that Islamic law may offer to further protect children from Child Labor. For that purpose, the analysis will involve examination on Islamic Perspectives on the role of the government in combating Child Labor what are the preventive measures that may be undertaken in order to prevent Child Labor.